Brief principles of macroeconomics - Mankiw, N. Gregory (Thomson/South-Western, 2004)
For professionals who prefer less coverage of micro topics than is offered in Mankiw's highly acclaimed textbook Principles of Macroeconomics, Mankiw now provides an excellent resource in this briefer version. Mankiw's principle texts have been praised as "perhaps the best ever" coverage in economic principles. The author's conversational writing style is superb for presenting the politics and science of economic theories. This book stands out among all other texts because of its ability to intrigue readers and encourage individuals to incorporate an economic way of thinking in daily life